Secondhand smoke levels in public building main entrances: outdoor and indoor PM2.5 assessment. Issue 6 (28th September 2011) - Sureda, Xisca; Martínez-Sánchez, Jose M; López, María José; Fu, Marcela; Agüero, Fernando; Saltó, Esteve; Nebot, Manel; Fernández, Esteve
Abstract : Background/Objectives: To describe secondhand smoke (SHS) levels in halls and main entrances (outdoors) in different buildings by measurement of PM2.5 and airborne nicotine. Methods: Cross-sectional study in a sample of 47 public buildings. The authors studied SHS levels derived from PM2.5 (micrograms per cubic metre) using TSI SidePak Personal Aerosol Monitors. The authors tested four locations within buildings: hall, main entrance (outdoor), control (indoor) and control (outdoor). The authors also measured airborne nicotine concentration (micrograms per cubic metre) in main entrances (outdoor). The authors computed medians and IQRs to describe the data. Spearman correlation coefficient (rsp) was used to explore the association between PM2.5 concentrations simultaneously measured in halls and main entrances as well as between PM2.5 and nicotine concentrations. Results: The authors obtained an overall median PM2.5 concentration of hall 18.20 μg/m 3 (IQR: 10.92–23.92 μg/m 3 ), main entrance (outdoor) 17.16 μg/m 3 (IQR: 10.92–24.96 μg/m 3 ), control (indoor) 10.40 μg/m 3 (IQR: 6.76–15.60 μg/m 3 ) and control (outdoor) 13.00 μg/m 3 (IQR: 8.32–18.72 μg/m 3 ). The PM2.5 concentration in halls was more correlated with concentration in the main entrances (outdoors) (rsp=0.518, 95% CI 0.271 to 0.701) than with the control indoor (rsp=0.316, 95% CI 0.032 to 0.553). The Spearman correlation coefficient between nicotine and PM2.5 concentration was 0.365 (95% CI −0.009 to 0.650). Conclusions: Indoor locations where smoking is banned are not completely free from SHS with levels similar to those obtained in the immediate entrances (outdoors) where smoking is allowed, indicating that SHS from outdoors settings drifts to adjacent indoors. These results warrant a revision of current smoke-free policies in particular outdoor settings.